Centerbridge - Rosenthal, Jean W., 1945- (London : SAGE Publications Ltd, 2017)
When Jeffrey Aronson and Mark Gallogly founded Centerbridge in 2005, they hoped to grow the New York City-based, private investment firm to a point it was big enough to matter, but not so large as to lose the firms nimbleness and collegial culture. By joining Aronson's experience in debt investing and Gallogly's background in private equity, the two men believed they could build a firm that could approach opportunities in a uniquely flexible manner. Centerbridge could either make traditional private equity investments thus generally assuming a controlling stake in companies or make non-control investments by purchasing debt or other liquid securities in restructuring or bankrupt firms. The firm had the plasticity to adapt to changing financial conditions and the specific capital structure of target investments. The firm's name, Centerbridge, represented the joining of the two investing approaches.
Originally published: Rosenthal, J. (2015). Centerbridge. 15-015. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://vol11.cases.som.yale.edu/centerbridge.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Centerbridge; Investment advisors -- New York (State) -- New York